IMPLIKASI KEBIJAKAN PENGGABUNGAN KELURAHAN TAHUN 2015 – 2016 TERHADAP DINAMIKA SOSIAL DAN POLITIK DI KOTA PEKALONGAN - novia kristanti; nur hidayat sardini; kushandajani . (Journal of Politic and Government Studies, 2016)
ABSTRACTPekalongan city is autonomous region, which means it has a self-governing management with respect to its local or internal affairs. Pekalongan city establishes a sub district merger policy in order to create public service effectiveness and budget efficiency. This research aims to describe the implication of implementation sub district merger policy toward social and political dynamics in Pekalongan city.The type of this research is analysis descriptive. Qualitative approach is applied, to describe situation or phenomenon in details. The data sources used are primary and secondary data. Informants are chosen using purposive sampling method. Informants are people who have knowledge, experience, and deep insight to the political and social dynamics of sub district merger policy in Pekalongan city. This research uses 3 (three) methods to collect the data: interview, observation, and document study.The results of this research find that the implication of implementation sub district merger policy by Pekalongan city government causes vertical and horizontal conflict. The sub district merger policy in Pekalongan city causes changes of region nomenclature. Pekalongan citizen who highly give respect to cultural values, considered that the change of region nomenclature imply the abolishment of the history.The dispute of sub district merger policy happened when Pekalongan’s mayor and vice mayor Election Day. Some candidates use this opportunity to acquire society sympathy by giving campaign related the solution of the dispute of sub district merger policy.This research suggest to Pekalongan city government to involve the society as the policy object to their decision making process, so that the following policy will not rise the conflict for the executive and legislative.Keywords: public policy, sub district merger, conflict